Larval trematodes (Digenea) of the great pond snail, Lymnaea stagnalis (L.), (Gastropoda, Pulmonata) in Central Europe: a survey of species and key to their identification - Faltýnková, A; Nasincová, V; Kablásková, L (Parasite (Paris, France), 2007)
A survey of cercariae and metacercariae (Trematoda, Digenea) from the great pond snail (Lymnaea stagnalis) in Central Europe (Austria, Czech Republic, South-East Germany, Poland and Slovak Republic) is presented, based on a study of 3,628 snails examined from 1998 to 2005. A total of 953 (26.3%) L. stagnalis were infected with 24 trematode species comprising 19 species of cercariae and 11 species of metacercariae (six species occurred both as cercarie and metacercarie) of eight families. The dominant cercariae were those of Opisthioglyphe ranae (159 hosts infected), Plagiorchis elegans (141) (both family Plagiorchiidae) and Echinoparyphium aconiatum (153) (Echinostomatidae); 14 double infections were found. The most frequent metacercariae were those of Neoglyphe locellus (71) (Omphalometridae), E. aconiatum (66), Echinostoma sp. (59) and Moliniella anceps (48) (Echinostomatidae). In the previous studies carried out in Central Europe, a very similar spectrum of nine trematode families of 22 cercariae determined to species level and 43 types of cercariae reported under generic or provisional names, which can be in many cases conspecific with the previous taxa, were found. A simple key to identification of cercariae and metacercariae, together with their illustrations, is provided.
Keywords: larva; Evropa; Animals; mužské pohlaví; Larva; Species Specificity; ženské pohlaví; druhová specificita; Lymnaea; zvířata; Sentinel Surveillance; Female; Phylogeny; fylogeneze; Europe; Male; sentinelová surveillance; Trematoda